Fungal community enhanced humification and influenced by heavy metals in industrial-scale hyperthermophilic composting of municipal sludge. (September 2022) - Huang, Yu-Hong; Chen, Xiao-Hong; Li, Qi-Fang; Lü, Huixiong; Mo, Ce-Hui; Feng, Nai-Xian; Xiang, Lei; Zhao, Hai-Ming; Li, Hui; Li, Yan-Wen; Cai, Quan-Ying
Graphical abstract: Highlights: Fungal community displayed dynamic change during hyperthermophilic composting. Fungal community experienced stochastic and deterministic assembly processes. Heavy metals displayed essential effect on fungal community during composting. Keystone fungi and potential drivers for humification were identified. Some keystone taxa and drivers were thermophilic- and heavy metal-resistant fungi. Abstract: The succession of fungal community and effects of heavy metals on fungi during industrial-scale hyperthermophilic composting of municipal sludge remain unclear. Results showed hyperthermophilic composting enhanced decomposition and humification of municipal sludge in the short terms, while heavy metal concentrations and speciation had no significant change with high copper and zinc levels (101–122 and 292–337 mg/kg, respectively) in compost samples. The fungal community and its ecological assembly displayed dynamic change during hyperthermophilic composting. Some thermophilic-resistant fungi, such as phylum Ascomycota and genera Candida, Aspergillus, Thermomyces and Petriella dominated in hyperthermophilic phase. Heavy metals served important effects on fungal community structure and functions during composting. Some fungal drivers (e.g., Thermomyces, Petriella and Schizophyllum ) and keystone fungi (e.g., Candida and Pichia ) might be thermophilic- and heavy metal-resistant fungi which played important roles in decomposition and humification of municipal sludge. This study reveals fungal community accelerating humification and its influencing factors during composting.